2019
DOI: 10.1038/s41598-019-49780-z
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Nanomechanical Properties of Materials using Nanoindentation and Artificial Neural Network

Abstract: Mechanical properties of materials can be derived from the force-displacement relationship through instrumented indentation tests. Complications arise when establishing the full elastic-plastic stress-strain relationship as the accuracy depends on how the material’s and indenter’s parameters are incorporated. For instance, the effect of the material work-hardening phenomenon such as the pile-up and sink-in effect cannot be accounted for with simplified analytical indentation solutions. Due to this limitation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…Различным аспектам наномеханического поведения твердых тел и способам их исследования методами NI и SSMT посвящено большое число книг [13][14][15][16][17][18][19] и обзоров [20][21][22][23][24][25][26], опубликованных в последнее десятилетие. Поэтому концептуальные основы техники исследования наномеханических свойств материалов классическими методами NI описаны в настоящем обзоре кратко, в порядке введения к основному материалу.…”
Section: юи головинunclassified
“…Различным аспектам наномеханического поведения твердых тел и способам их исследования методами NI и SSMT посвящено большое число книг [13][14][15][16][17][18][19] и обзоров [20][21][22][23][24][25][26], опубликованных в последнее десятилетие. Поэтому концептуальные основы техники исследования наномеханических свойств материалов классическими методами NI описаны в настоящем обзоре кратко, в порядке введения к основному материалу.…”
Section: юи головинunclassified
“…Existing researches 5,21 showed that indentation measurement has implicit response parameters derived from the load and unload curve from nanoindentation which can be inter-related using the dimensional function approach based on the work by Cheng and Cheng 22 . Conventionally, the indentation modulus (M) and hardness (H) results are calculated from this force and displacement response using the popular Oliver-Pharr method 23,24 .…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Firstly, the cohesive-strength homogenisation model in Level I is applied for the continuum discretisation of instrumented indentation solution. The instrumented indentation is a well-known technique that has emerged for determining mechanical properties 17,18 . Recently, the instrumented indentation makes it possible to test the structure of porous materials with the characteristic size of porosity much smaller than the maximum indentation depth 19 .…”
Section: Application Of Cohesive-strength Homogenisationmentioning
confidence: 99%
“…Nanoindentation test was conducted on the three sets of cube specimens with XP BASIC testing mode with Keysight Nanoindentation G200; each set was specified around 300 indentation points on the cementitious matrix, fine sand and coarse aggregate using the Berkovich indenter. The hardness values of each indentation point then determined using our inverse algorithm 18 695 GPa, respectively. he present results show that even though M1 and M2 matrices have the same mix design, Level 0 (solid) properties are not consistent to each other.…”
Section: Application Of Cohesive-strength Homogenisationmentioning
confidence: 99%
See 1 more Smart Citation